Hemostatic effect of oxidized regenerated cellulose in an experimental gastric mucosal resection model - Velázquez-Aviña, Jacobo; Mönkemüller, Klaus; Sakai, Paulo; Sulbaran, Marianny; Chávez-Vargas, Carlos; Montalvo Javé, Eduardo; Sobrino-Cossío, Sergio (Endoscopy, 2014)
Background and study aim: The endoscopic hemostatic therapies currently available do not always result in hemostasis of gastrointestinal bleeding. Oxidized regenerated cellulose (ORC) mesh is a widely available surgical hemostatic material. The aim of this study was to evaluate the hemostatic efficacy of ORC in experimental gastric hemorrhage after endoscopic resection.Methods: This was a prospective, two-stage experimental, Phase I, proof-of-concept study. In Stage 1, eight gastric mucosal lesions were created in anticoagulated rabbits and treated with ORC (closed or open pores). In Stage 2, the endoscopic introduction and application of ORC mesh pieces were evaluated in a porcine model of endoscopic submucosal dissection (ESD).Results: In Stage 1, hemostasis was achieved in all lesions. Hemostasis was achieved more rapidly with closed-pore than open-pore ORC (24.5 vs. 66.5 seconds) (P < 0.01). At 24 hours, all lesions showed persistent hemostasis. There were no episodes of rebleeding, complications, or mortality. In Stage 2, the endoscopic introduction of ORC pieces and application with a biopsy forceps were feasible in all ESD lesions. Conclusions: ORC was an effective hemostatic agent for bleeding lesions following mucosal resection in anticoagulated rabbits. Closed-pore ORC achieved hemostasis faster than open-pore ORC. Endoscopic introduction and release of ORC were feasible.